Coexistence paradigm of the technological catching up process - Xiong, Jie; Xu, Lu; Yan, Jie; Chakraborty, Shubho; Gong, Yeming (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
Established studies on catching up have mainly overlooked a comprehensive understanding of the process. We examine the Chinese auto parts manufacturing industry’s technological catching up to derive conclusions about the development paradigm. We address this conundrum by employing a process-based case study to extend the theory of technological catching up. This leads us to call this alternative paradigm coexistence. Coexistence encompasses various interactions between new and old generations in the process of catching up. In our findings, we propose three coexistence scenarios, namely: convergent, asymptotic, and intersectional.